2021
DOI: 10.1155/2021/6658211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rainfall Pattern and Crack on the Stability of a Red Bed Slope: A Case Study in Yunnan Province

Abstract: Red bed slopes in the southwest of China are associated with a grant number of geological hazards, such as landslides, mud-rock flows, and rock blocks falling, which are vital problems in geotechnical engineering. The damage can be induced or triggered due to a series of human and environmental activities, such as excavation, concentrated or long-term rainfall, earthquake, and fluctuation of groundwater level. According to the field observations and geological exploration results, a small-scale landslide was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Reservoirs and water diversion engineering channels are widely distributed and often need to run through the red-bed distribution area. Te red-bed soft rock is prone to cracks, swelling, slope collapse, and other problems [6,7], afecting the normal water delivery and operation safety of the water channel. Under long-term operation conditions, the sediment denuded from the channel sidewall is prone to siltation along the way through the fow transportation in the channel, which seriously leads to the elevation of the channel bottom, the increase of the channel width, and the reduction of the berm [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Reservoirs and water diversion engineering channels are widely distributed and often need to run through the red-bed distribution area. Te red-bed soft rock is prone to cracks, swelling, slope collapse, and other problems [6,7], afecting the normal water delivery and operation safety of the water channel. Under long-term operation conditions, the sediment denuded from the channel sidewall is prone to siltation along the way through the fow transportation in the channel, which seriously leads to the elevation of the channel bottom, the increase of the channel width, and the reduction of the berm [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…According to Dietze et al (2014), soluble sugar can be used as a direct carbon source for transportation and plant use. Thus, soluble sugar indicates the plant's ability to buffer environmental fluctuations (Zhang et al, 2021) by reflecting the balance between carbon intake and consumption (Würth et al, 2005). In the same way, soluble sugars influence the growth and development of plant tissue, both generative and vegetative.…”
Section: Relationship Between Morphological and Leaf Physiological Tr...mentioning
confidence: 99%
“…Rainfall is also an important factor affecting the stability of dam slopes, 17 which increases the water content of the soil surface and reduces the strength parameters of the surface soil, thereby reducing the slope safety factor of the dam. Zhang et al 18 and Elkamhawy et al 19 found that during rainstorm, the stability of the slope decreases, the rainfall infiltration leads to the decrease of soil shear strength, through monitoring the positive pore water pressure and horizontal earth pressure of soil under rainfall conditions. 20,21 Besides, Huang et al 22 performed a numerical simulation to calculate the stability coefficient of the Three Gorges Project affected by reservoir water level fluctuations and rainstorms.…”
Section: Introductionmentioning
confidence: 99%